2023
DOI: 10.1108/jbim-12-2021-0536
|View full text |Cite
|
Sign up to set email alerts
|

Does service modularity enhance new service development performance in supply chains: an empirical study

Abstract: Purpose Customer firms and suppliers are valuable knowledge resources that can be used for achieving superior new service development (NSD) performance. This study aims to investigate how supply chain relationship quality (SCRQ) and knowledge sharing promote the success of NSD, and examines service modularity as an important contingency factor that enhances NSD performance in supply chains. Design/methodology/approach Based on service-dominant logic, this study builds a conceptual model to empirically explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
(230 reference statements)
0
3
0
Order By: Relevance
“…2023, 13, x FOR PEER REVIEW 3 of 17 on manufacturing lead time and throughput rate, but only marginally in other related domains (e.g., Refs. [27][28][29][30][31]). Experiences from Danish manufacturing companies showed that modularity principles are mostly applied in complex manufacturing processes, and that high levels of implementation of JIT shorten lead times, as might be expected [32].…”
Section: Methodology and Research Object Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…2023, 13, x FOR PEER REVIEW 3 of 17 on manufacturing lead time and throughput rate, but only marginally in other related domains (e.g., Refs. [27][28][29][30][31]). Experiences from Danish manufacturing companies showed that modularity principles are mostly applied in complex manufacturing processes, and that high levels of implementation of JIT shorten lead times, as might be expected [32].…”
Section: Methodology and Research Object Specificationmentioning
confidence: 99%
“…In the latest years, some articles investigated the positive modularity impacts on manufacturing lead time and throughput rate, but only marginally in other related domains (e.g., Refs. [27][28][29][30][31]).…”
Section: Related Workmentioning
confidence: 99%
“…Some of these innovations include the development of alternative distribution channels, the use of digital platforms for supply chain coordination and the adoption of new technologies for food safety and traceability (Akao, 2004). The shifting of FSCs to local or regional sourcing and strengthening them helps reduce reliance on international supply chains and, in turn, also helps in getting a source of revenue for the local people (Osman and Jian, 2023).…”
Section: Implications Of the Studymentioning
confidence: 99%